Educational and aesthetic data in school murals Directorate of Public Education, Al-Rusafa/Third (Al-Academy, 2025)
Human interest in murals is due to deep intellectual roots, in addition to their educational and aesthetic value for students. The school environment will also include inspiring visual elements that contribute to awakening enthusiasm, happiness and activity among students. This effect comes from the need to absorb, perceive and receive the educational and aesthetic elements of the mural that it contains As the student represents the target part, and thus attracts the eyes of students in the school mural, the real effectiveness gained by the elements and their influence comes depending on the quality of the mural and the amount of treatment. The orientation is represented according to the relationship itself, which can be achieved within the student's imagination, as well as what these visual formations raise for the mural, and what its cognitive function achieves in terms of meanings, symbols and indications embodied in the student. The importance of the school mural, and its priorities follow the design treatments of the teachers and teachers of art education. Therefore, the research problem was revealed by the following question:(What is the role of school murals in general education, the third Rusafa)?While the goal of the research was determined in: (identifying the school murals and what they achieve in general education, the third Rusafa), the theoretical framework focused on several topics, as the first topic dealt with: (the educational data of the school murals in the General Directorate of Education, the third Rusafa), and the second: (the aesthetic data of the murals School in the General Directorate for Education Rusafa III) and the third: (types of school murals), then three models were described and analyzed, based on the paragraphs of the analysis derived from the theoretical framework, and the indicators that resulted from it.